Evaluating The Efficacy of Citrus Lemon (Lemon Fruit) And Syzgium Aromaticum (Clove Seed) Combination as A Natural Mosquito Repellent (International Journal of Scientific Research in Science and Technology, 2024)
This study investigated the efficacy of Citrus lemon (lemon fruit) and Syzgium aromaticum (clove seed) combination as a natural mosquito repellent. Fresh and healthy parts of the plants were collected and shade dry before pulverizing into fine powder. The pulverized samples were extracted with ethanol. The qualitative and quantitative analysis and mosquito repellent capacity were determined. Repellency assay was performed using different treatment concentrations (100%, 75%, 50%, and 25%), while distilled water served as a control. Qualitative analysis revealed the presence of flavonoids, saponins, tannins, alkaloids, cardiac glycosides, and steroids in both extracts. Quantitative analysis indicated varying yields of phytochemicals. In Citrus lemon extract, saponin had the highest yield (1.08g) at 3.6 mg/g, followed by flavonoids (1.00g) at 0.26 mg/g, tannins (0.64g) at 1.7 mg/g, and alkaloids (0.24g) at 0.54 mg/g. Syzgium aromaticum extract showed saponin as the most abundant compound (1.02g) at 3.09 mg/g, followed by tannins (0.62g) at 1.8 mg/g, alkaloids (0.22g) at 0.50 mg/g, and flavonoids (0.07g) at 0.5 mg/g. Repellency assays demonstrated significant efficacy of both extracts. In Citrus lemon extract, at 100% concentration, 115 mosquitoes were repelled, followed by 70% (97), 50% (62), and 25% (29) concentrations. The control (distilled water) repelled 2 mosquitoes. Similarly, in Syzgium aromaticum extract, at 100% concentration, 123 mosquitoes were repelled, followed by 70% (109), 50% (53), and 25% (26) concentrations, with the control repelling 2 mosquitoes. Combining the extracts significantly enhanced repellency efficacy, with a total of 223 mosquitoes repelled at 100% concentration, followed by 200 at 70%, 116 at 50%, and 81 at 25%. Statistical analysis confirmed significant differences (p<0.05) in repellency efficacy at various concentrations. These findings highlight the potential of Citrus lemon and Syzgium aromaticum extracts as natural mosquito repellents, suggesting their viability in vector control strategies.